About Strategy of Development of a Sanatorium Complex of the Russian Federation (Analysis of the Tasks and Their Solutions) - D. Yu. Desyatnichenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article investigates the improvement of the draft strategy for the development of the Russian Federation’s sanatorium and Spa complex. The authors have made a number of practical proposals aimed at adjusting and complementing the objectives of the strategy, justifying them by means of comparative analysis using the relevant data from tourism statistics in Russia and abroad; Development of mechanisms for effective coordination of the activities of the executive authorities at all levels in the implementation of activities for the conservation of resorts, therapeutic and recreational areas and natural health resources, their integrated territorial Development also points to the need to adjust and develop new financial mechanisms and economic incentives in relations between citizens, health care institutions, insurance Companies and facilities at Spa and spa services, which should, in the new interest of citizens in the maintenance and repair of lost health, increase in the medium and long term the demand for the services of the domestic In domestic and global markets.The authors conclude that the implementation of the strategy will restore the therapeutic and curative function of Russian resorts, which has been lost during the years of market transformation, would have a positive impact on the logistics base of the SPA The set will increase the final demand and investment in a range of related sectors and sectors of the economy.